2017
DOI: 10.1039/c7ra02020a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a human acellular amniotic membrane loaded with mechanical stretch-stimulated bone marrow mesenchymal stem cells for the treatment of pelvic floor dysfunction

Abstract: Pelvic floor dysfunction (PFD) has a severe impact on the quality of life of middle-aged and elderly women and is closely related to the damage of pelvic support tissues, especially ligaments. The incidence of PFD is high in elderly populations. Conventional treatments are associated with high complication and relapse rates. Bone marrow mesenchymal stem cells (BMSCs) are bone marrow-derived pluripotent stem cells that can differentiate into many types of cells. We have found that when cultured with mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Finally, the hAM has been used as a scaffold for salivary gland regeneration, for esophageal wall tissue engineering, for the treatment of pelvic floor dysfunction, for liver regeneration, , and as a support of in vitro ovarian follicular culture …”
Section: Tissue Engineering Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the hAM has been used as a scaffold for salivary gland regeneration, for esophageal wall tissue engineering, for the treatment of pelvic floor dysfunction, for liver regeneration, , and as a support of in vitro ovarian follicular culture …”
Section: Tissue Engineering Applicationsmentioning
confidence: 99%
“…66,135,136 Consequently, several studies have reported rolling the hAM to engineer small diameter blood vessels. 34,60,66,67,137 Finally, the hAM has been used as a scaffold for salivary gland regeneration, 138 for esophageal wall tissue engineering, 139 for the treatment of pelvic floor dysfunction, 140 for liver regeneration, 141,142 and as a support of in vitro ovarian follicular culture. 143 ■ LIMITATIONS Risk of Disease Transmission.…”
Section: ■ Tissue Engineering Applicationsmentioning
confidence: 99%
“…According to their study, decellularized amnion increased the proliferation and differentiation of BMSCs, and caused effective improvement in the function of PFD rats. 42 Zheng et al prepared a 3D micronized (i.e., 300-600 μm micro-particles) scaffold of lyophilized decellularized amnion. According to their result, human dermal fibroblasts cultured in micronized amnion significantly improved vascularization and wound healing in mice diabetic wound models.…”
Section: Introductionmentioning
confidence: 99%
“…However, pure BMSCs show weak elastin protein secreting ability; thus, proper stimulus could be given to solve this problem. Gene transfection technique is well performed in cell science through transfecting target gene fragment to recipient cells; therefore, the BMSCs with high elastin expression capacity would be obtained [39][40][41][42]. However, due to the chemical inert surface and large holes of PP mesh, the genetransfected cells could not be loaded and implanted together to the injured tissue; thus, certain method should be developed to deal with this problem.…”
Section: Introductionmentioning
confidence: 99%